Nanoimprinted Materials for Nanoparticle Sensing and Removal - Lavinia Doveri; Azhar Mahmood; Piersandro Pallavicini (Nanomaterials)
The booming expansion of nanotechnology poses the problem of environmental pollution by nanoparticles (NPs). The available methods for sensing and removing NPs from the environment are typically lengthy and instrumentally demanding. The recent introduction of NP-imprinted polymers (NPIPs), either as films or bulk materials, is an important step toward the simple and fast sensing and removal of NPs from water and air. Similarly to the well-established molecularly imprinted polymers, in NPIPs, an organic or inorganic polymeric material is first obtained with embedded NPs. Then, the NPs are chemically or physically removed by acting as a template, i.e., leaving a polymeric matrix with cavities of the same shape and dimensions. After the first examples were published in 2014, the literature has so far reported an increasing number of NPIPs that are capable of reuptaking NPs from water (or, more rarely, air), with remarkable size and shape selectivity. By laying an NPIP layer on a reporter (typically an electrode), devices are obtained that are capable of sensing NPs. On the other hand, bulk NPIPs can reuptake massive amounts of NPs and have been used for the quantitative removal of NPs from water. This review begins with an overview of NP-imprinted hollow capsules, which can be considered the ancestors of NPIPs, both as conception and as preparative methods. Then, the literature on NPIPs is reviewed. Finally, the possible evolutions of NPIPs are highlighted from the perspective of stepping toward their real-life, field use.